Isolation and characterization of LEAFY homologous gene partial sequences from Dendrobium capra J.J. Smith Endemic Orchid of Java Island - Muhammad Dylan Lawrie; Ari Indrianto; Aziz Purwantoro; Endang Semiarti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2018)
Dendrobium capra is an endemic orchid species on the island of Java, Indonesia, which blooms only once a year, usually in February. In the flowering process, LEAFY (LFY) gene and its homologs are considered as key regulators in flowering of higher plants, including orchids. To understand floral regulatory mechanisms in orchids, information on the flowering gene structure needs to be explored. Partial sequences of LFY homologue of D. capra has been isolated and consists of 220 bp encoding 72 amino acid sequences. Bioinformatic analysis using Blastp search showed high similarity between the LFY genes of D. capra with other orchid LFY genes and has adjacent evolutionary relationship among orchid’sLFY. Amino acid sequence alignment result showed similar characteristic with other orchid’s LFY with conserved motif leucine-rich repeat and DDPRRRLLLLSPDQHN amino acid motif.